Patterns of Communication with Reference to Gender in Cooperative Learning Classroom - Tri Indah Rezeki; Amrin Saragih; Sri Minda Murni (Universitas Negeri Medan, 2014)
The main objectives of this research are to investigate patterns of communication with reference to gender in Cooperative Learning Classroom and to find out what contextual and psychological factors affect male and female students communicate in “report” type talk and “rapport” type talk in CL Classroom. The method of this study was descriptive qualitative research. The source of data was the students of the eighth grade of Ar-Rahman Junior High School in Percut. There was one CL classroom which consists of three groups with the total number of students is 15 students namely 8 female students and 7 male students. The data were collected by recording CL classroom, transcribing the male and female utterances and identifying communication patterns of male and female in CL classroom. The findings of the study are a) there are 17 sentences of male students communicate in “report” type talk and 15 sentences of female students communicate in “report” type talk; b)) there are 28 sentences of female students communicate in “rapport” type talk and 11 sentences of male students communicate in “rapport” type talk; c) contextual factor which is the type of evaluation/rewards is the most important role in male and female communication in classroom. Keywords: Male Communication Patterns, Female Communication Patterns, Cooperative Learning Classroom, Contextual Factors in Cooperative Learning, Psychological Factors in Cooperative Learning